Light transmission through UV Coated Contact Lenses - Bariah Mohd Ali,; Goh E.H, (Department Of Community Health, Faculty of Medicine, Universiti Kebangsaan Malaysia, 2002)
The objective of this study was to determine the efficiency of UV blocking monomers in contact lenses in providing eye protection from UV radiation. The spectral transmission of 8 contact lenses (7 soft contact lenses: Precision UV, Acuvue 2, Surevue, Omega, Encore UV, Durasoft 3 and Lunelle UV and 1 rigid gas permeable contact lens: Boston 7) was evaluated by using a dual beam spectrophotometer. Durasoft 3, a non UV absorbent contact lens was used as the control. The results showed that Precision UV contact lens absorbed UV light up to wavelength of 380 nm, whereas Acuvue 2 and Surevue absorbed upto 360 nm only. Omega, Encore UV and Lunelle UV lenses absorbed UV light up to 335 nm with spectral transmission of Lunelle UV being the highest among all soft contact lenses tested, which was 17%. Boston 7 could absorb UV light up to 385 nm, but the amount of UV light transmitted was higher than soft lenses, which was 30%. Durasoft 3 only blocked UV light at 200-245 nm. Precision UV lens had better UV blocker characteristics than the other contact lenses tested. UV blocking soft contact lenses could be an alternative for spectacles in protecting internal ocular structures from UV radiation.